2017
DOI: 10.3329/bjp.v12i4.33652
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the chemical composition and antimicrobial activity of Frankenia hirsuta

Abstract: <p class="Abstract">Frankenia hirsuta is widely located in Turkey, but the antimicrobial potential and biochemical composition analysis of it weren’t determined yet. By using the disk diffusion method, the susceptibility of 17 bacteria and 1 fungi were analyzed, which included Bacillus, Candida, Enterobacter, Enterococcus, Esche-richia, Klebsiella, Listeria, Pseudomonas, Salmonella and Staphylococcus genera. 0.8, 1.5 and 3.1 mg of samples were prepared by using absolute ethanol. The bioactive composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
(16 reference statements)
0
18
0
Order By: Relevance
“…With the aim of preventing to spread these microorganisms, which are resistant to commercially used antimicrobials, characterization of new antimicrobial agents is proposed as the major aim for the scientists (Özkinali, Şener, Gür, Güney & Olgun, 2017;Canlı, Şimşek, Yetgin & Altuner, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of preventing to spread these microorganisms, which are resistant to commercially used antimicrobials, characterization of new antimicrobial agents is proposed as the major aim for the scientists (Özkinali, Şener, Gür, Güney & Olgun, 2017;Canlı, Şimşek, Yetgin & Altuner, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Disc diffusion is a basic and important laboratory method which can be used routinely to screen the antibacterial activity of a compound in vitro (Balouiri et al, 2016;Canli et al, 2017). The study confirmed that cell-free culture supernatant of DD_A7 has the potential to diffuse from the disc and can effectively control the growth of the pathogenic E. coli.…”
Section: Before Treatmentmentioning
confidence: 77%
“…Antimicrobial Assay: Antimicrobialanalysis was followed using a standard agar well diffusion method to study the antimicrobial activity of compounds 31,33 . Each bacterial isolate was suspended in Brain Heart Infusion (BHI) broth and diluted to approximately 10 5 colony-forming units (CFU) per mL.…”
Section: Synthesis Of [Cu(phen)(tryp)scn] (3)mentioning
confidence: 99%